(untitled) (Bangladesh Journal of Medicine, 2022)
Background: Tuberculosis (TB) remains a major, worldwide, public-health problem in the 21st century. Patient non-compliance is a major barrier to the control of TB, treatment of individual patients and in the development of drug resistance. The reasons for poor compliance are complex, ranging from characteristics of individual patients to qualities of social economic environment of the patient and the health service. Methods: An observational, cross sectional study was carried out in the Department of Medicine in Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka during the six months period. Results: The average age group of compliance patients is between 46-55 years and between 26-45 among the defaulter group. The gender, marital and employment status were not significantly associated with compliance. Furthermore the study also show that the majority (35%) of compliance group reside at distances less than 5 km. from the TB centre while the majority from the defaulters (92%) resided over 15 km. Multiple logistic regression analysis showed the barriers to TB treatment include: disbelief in the fact that TB can result in death if not treated, belief in traditional medicine for curing TB, bad healthcare worker attitudes, long distance to the clinic for treatment, belief that TB treatment takes very long and the pill burden. Conclusion: Knowledge, patient-provider communications, social support and accessibility might have played significant roles in the low completion rate of TB treatment. Planned interventions targeted at these factors should be implemented with their effects carefully monitored to improve current TB control in Bangladesh. Bangladesh J Medicine 2022; 33: 168-175